Trust Factor Based Secure Congestion Control For Vanet (International Journal of Engineering and Computer Science, 2016)
Weight-based clustering algorithm in ad hoc network is an on demand clustering algorithm for multi-hop packet radio network. These types of networks are ad hoc networks and dynamic in nature due to mobility of nodes. Clustering in mobile ad hoc network can be defined as various partitions into various groups. It is an important concept of VANNET, because clustering makes it possible to guarantee of system performance, such as throughput delay and also security issues. So in the algorithm they select the cluster head whose performance is well and formation of cluster in ad hoc network. The cluster head is elected based on weight factor, so it is called weighted clustering algorithm. Weighted clustering algorithm is basically appropriate cluster selection in wireless adhoc network where it is necessary to provide robustness in face of topological changes caused by node motion, node failure and node insertion or node removal. The WCA select the cluster head which has lowest weight among the nodes and some other factor also consider the election for cluster head. The cluster head, form a dominant set in the network, determine the topology and its stability. The weighted clustering algorithm takes into consideration the ideal degree, transmission power, mobility and battery power of nodes. Traffic efficiency applications are becoming increasingly popular over the road networks in the last few years. This type of applications aims mainly at increasing the traffic fluency over the road network, which minimizes the travel time of each vehicle towards its targeted destinations. The Vehicular Ad-Hoc Networks (VANETs) technology has been utilized to design these applications. Communications between vehicles, V2V, and between vehicles and installed Road Side Units (RSUs), V2I, helped designing these applications. Malicious, selfish and intruder drivers can take advantages of other cooperative drivers and use their trust. a Secure Congestion control protocol. This protocol aims to guarantee integrity and authenticity of transmitted data. It is designed to provide the security requirements of traffic efficiency protocols that have been proposed using the technology of VANETs. SCOOL also aims to preserve the privacy of the cooperative vehicles and drivers. The main contribution of work is new strategy for clustering a wireless ad hoc network and improvement in WCA. Author derived a simple stability model and a load balancing clustering scheme. They showed that the algorithm outperform in term of cluster formation and stability. Main idea of approach is to avoid cluster re-election and reduce the computation and communication cost. The improved weighted clustering algorithm, the goals of algorithm are maintaining stable clustering structure, minimizing the overhead for clustering set up, maximize lifetime of nodes in the system and achieving good performance.